Transcending the Virtual Mirror Stage: Embodying the virtual self through the digital mirror - Desnoyers-Stewart, John; Smith, Megan L.; Riecke, Bernhard E. (Digital Research in the Humanities and Arts (DRHA) conference, 2019)
Mirrors have long provided access to virtual space. Well established in everyday life and artists’ tools, the optics of these planar surfaces present an interface to interact with and understand ourselves through the virtual image. They simultaneously externalize and alienate the self from an objective body while situating it within, and connecting it to, a larger whole. The mirror reminds us of our likeness and difference to other human bodies and that which surround us (Lacan, 1949). Most importantly, it makes concrete the embodied mind’s presence in reality. The ongoing proliferation of immersive technologies enable a more intimate, embodied connection with an ever-expanding multiplicity of virtual spaces. These technologies blur the distinction between virtual and actual reality, allowing a physical exploration of cyberspace; however, in entering the virtual space, identity can become disconnected. In many current immersive experiences, the body disappears, represented instead by only hands or controllers. These distal and ethereal means of interacting with the virtual threaten our embodied selves with a translucent existence. Providing a body in virtual reality (VR) can create a greater sense of presence by acknowledging the immersant’s desire and need for virtual embodiment. Yet the body may remain estranged and even ignored due to its situation in the periphery of the immersant’s restricted vision. In VR, we can make bodies more fluid, ethereal, and abstract than the immersant is accustomed to, and as such, a mechanism to establish a connection between the self and its virtual embodiment is needed. Transcending Perception is an immersive installation that uses body tracking combined with a VR headset and projection to allow immersants to use their bodies as instruments, producing abstract images and sound. The projections act as mirrors, presenting a real-time reflection of the virtual space, establishing its physicality and immersants’ presence within it. Immersants are connected to co-located abstractions of their body through this mirror metaphor which persists in the virtual imagery of the VR headset. This tool works to create the immersant’s digital identity by establishing a sense of ownership over the reflected virtual body. It situates their embodied self within the virtual environment presented in the mirror space, authenticated by the familiar connection between the virtual image and reality. Moreover, the two-dimensional nature of the mirror affords its existence both within the reality presented by a VR headset, and as a projected digital mirror outside of the headset. As an object with mixed realities, the virtual mirror projects the virtual space back outwards, allowing it to take on real, physical space. In this paper, we propose the capacity of the mirror to embody immersants within digital bodies, allowing them to enter virtual space, and enabling the virtual to permeate into physical space. Framed by Transcending Perception, and contextualized amongst other immersive digital artworks and technologies, we will support this theoretical discussion through the philosophy of Lacan and Foucault while grounding it in psychological research. Mirror space allows for navigation between digital and physical environments, by establishing a connected identity, and embodied virtual self.
Keywords: Riecke; Riecke_2019; bernhard-riecke; conferencePapers; conferenceTalksWithoutPaper; john-desnoyers-stewart; megan-smith; proj-transcending-perception; transcending-perception